UPAYA KEPALA MADRASAH DALAM MENSUKSESKAN PENERAPAN KURIKULUM 2013 - Imam Asrori (UNIVERSITAS BENGKULU, 2016)
The purpose of this study is to describe the problem in the success of efforts Principals curriculum implementation in 2013 in Madrasah Aliyah Lubuklinggau. Methods of data collectiontechniques in qualitative research is qualitative data collection observation, interviews, personal and official documentation, photographs, image recording, and informal conversations all the qualitative data. Conclusions this study shows that efforts are techniques to teachers, disseminate to related and those that act, and cooperation to the relevant parties, such as the Department ofEducation, implementation, to the publishers, submit a proposal pempersiapkan instructional media.Keywords: Principal, Curicculum 2013